Risk of coronary artery disease and stroke according to sex and presence of diabetic nephropathy in type 1 diabetes. Issue 12 (7th August 2018) - Harjutsalo, Valma; Thomas, Merlin C; Forsblom, Carol; Groop, Per‐Henrik; ,
Abstract : Aims: To determine the effect of different stages of diabetic nephropathy (DN) and sex on the excess and absolute morbidity of coronary artery disease (CAD) and stroke in people with type 1 diabetes (T1D) in order to distinguish different cardiovascular disease (CVD) risk profiles in people with T1D. Materials and Methods: The study included 4410 people with T1D from the Finnish Diabetic Nephropathy Study (FinnDiane), divided by DN status, and a control population of 12 434 people without diabetes. CVD events were identified from the Finnish nationwide health registries. Cumulative incidences for CAD and stroke were calculated and standardized incidence ratios (SIRs) were estimated between participants with T1D and the control group, stratified by DN status and sex. Results: There were 487 incident CADs and 290 strokes at the end of 2014 (median follow‐up 12.9 years). The cumulative incidence rates of CAD and stroke were similar in men and women within different nephropathy groups. The SIR for CAD was 7.5 (95% confidence interval [CI] 6.9‐8.2), 17.2 (95% CI 14.9‐19.5) in women and 5.3 (95% CI 4.7‐5.9) in men. The women‐to‐men ratio of SIR increased by nephropathy group: 3.3, 3.7, 5.3 and 6.8 in the normo‐, micro‐ and macroalbuminuria and end‐stage renal disease (ESRD) groups, respectively. The SIR for stroke was 5.0 (95% CI 4.3‐5.5), similar in men and women. The women‐to‐men ratio of SIR for stroke was 0.8, 1.3, 1.6 and 1.7, in the normo‐, micro‐ and macroalbuminuria and ESRD groups, respectively. The SIR in participants with normoalbuminuria and an estimated glomerular filtration rate ≥90 mL/min/1.73 m 2 was 3.5 (95% CI 2.5‐4.5) for CAD and 1.6 (95% CI 1.0‐2.3) for stroke. Conclusions: Although the excess CVD risk is several‐fold greater in women compared to men, the absolute CVD risk in men and women was equal when nephropathy was taken into account. Even participants with normoalbuminuria and normal kidney function were found to have an excess CVD risk compared with the control group without diabetes.